Relationship between gang involvement and mental health: a study with adolescents - Teixeira, Maria Inês Oliveira (2024)
Background: Callous-unemotional (CU) traits identify a subgroup of youth with severe and persistent patterns of antisocial behaviour that present unique characteristics that can be a challenge to intervene with. To get a sense of the interventions in youth with CU traits, a systematic literature review was conducted. Methods: The online databases EBSCOhost, PubMed, and Web of Science were used. Following the PRISMA 2020 guidelines, studies with a range of settings and participants, that adopted a randomized controlled trial, a controlled trial, or an open trial design and that examined if treatment had impact on CU traits were included. The Quality Assessment Tool for Quantitative Studies was used to assess risk of bias.Results: A total of 1573 studies were selected for eligibility analysis, with 20 articles being included in the final sample, published between 2011 and 2022. Most studies (n=10) found reductions in CU traits, while three studies did not. Regarding predictors and moderators, studies reported that high-CU was associated with worse outcomes and other three stated that youths did no better and/or worse in response to the treatment. Meanwhile, two studies reported positive treatment outcomes. Discussion: Overall, youth with CU traits benefit from treatment, but children with high levels of CU traits display a worse post-treatment than those with low CU traits. Language bias, variation in terms of setting, duration, modality, population, study design, and reports usage to access efficacy of intervention of the included studies were acknowledged as possible sources of bias.